2014
DOI: 10.1016/j.jocd.2013.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Simplified Criteria for Selecting Patients for Vertebral Fracture Assessment

Abstract: The 2013 Position Development Conference of the International Society for Clinical Densitometry (ISCD) has adopted simplified indications for vertebral fracture assessment (VFA) based on an analysis of the Study of Osteoporotic Fractures (SOF). This showed that a simpler regression model, which included only age, bone mineral density (BMD), and height loss, was able to differentiate women with vertebral fractures from those without vertebral fractures almost as well as more complex models. We aimed to verify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In Canada, Manitoba is the only province that currently systematically employs VFA as part of their provincial bone densitometry and fracture assessment protocols. VFA at the time of bone densitometry is inexpensive, convenient, point‐of‐care testing with minimal patient radiation exposure and minimal added bone technologist time commitment to perform . Our study and others have shown that bone density technologists can successfully implement a decision rule to identify those referred for bone densitometry as also appropriate candidates for VFA.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In Canada, Manitoba is the only province that currently systematically employs VFA as part of their provincial bone densitometry and fracture assessment protocols. VFA at the time of bone densitometry is inexpensive, convenient, point‐of‐care testing with minimal patient radiation exposure and minimal added bone technologist time commitment to perform . Our study and others have shown that bone density technologists can successfully implement a decision rule to identify those referred for bone densitometry as also appropriate candidates for VFA.…”
Section: Discussionmentioning
confidence: 68%
“…VFA at the time of bone densitometry is inexpensive, convenient, point-of-care testing with minimal patient radiation exposure and minimal added bone technologist time commitment to perform. (13,(41)(42)(43)(44) Our study and others (19,42) have shown that bone density technologists can successfully implement a decision rule to identify those referred for bone densitometry as also appropriate candidates for VFA. Prior studies that have shown that clinicians can be easily trained to identify vertebral fractures on lateral spine images.…”
Section: Journal Of Bone and Mineral Researchmentioning
confidence: 89%
“…(95) Several cross-sectional studies, with retrospective (n = 7) and prospective (n = 4) data collection, evaluated the prevalence of morphometric VFx in patients with PHPT (Table 2). (62,72,(96)(97)(98)(99)(100)(101)(102)(103)(104)(105) The cohorts enrolled between 98 and 588 patients, mostly postmenopausal women, age 59-73 years. Disease severity was either heterogeneously defined or not reported.…”
Section: Fracturesmentioning
confidence: 99%
“… Recruited among patients screened for VFA according to the 2013 NOF screening criteria by Chou and colleagues. ( 105 ) …”
Section: Introductionmentioning
confidence: 99%
“…81,82 However, VFA is gaining a lot of popularity and consensus, with cost-effective value, expanding indications, and its incorporation into a one-stop diagnostic pathway, as several authoritative authors and societies have testified (e.g., International Society for Clinical Densitometry official positions, 2013 and 2015). [83][84][85][86][87] Many differential diagnoses have to be considered in individuals with vertebral deformities. Several pitfalls can interfere with vertebral height measurement or evaluation.…”
Section: What Is the Impact Of Vertebral Fractures?mentioning
confidence: 99%